2019
DOI: 10.3390/su11184844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH Conditions and Application Rates of Commercial Humic Substances on Cu and Zn Mobility in Anthropogenic Mine Soils

Abstract: We studied the effects of commercial humic substances derived from leonardite at different rates (0, 0.25, 2, 10 g kg −1 ) and pH (4.5, 6.0, 8.0) on Cu and Zn mobility, to evaluate their use for remediation of metal contaminated mine soils and to optimize their application conditions. We conducted a single-step extraction experiment and analyzed extracts for metal concentrations, soluble organic carbon and their E4/E6 ratio (ratio of absorption at 465 to 665 nm). Metal speciation in a soil solution was simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
2
5
2
Order By: Relevance
“…The application of humic acid seemed to be preferred over fulvic acid in enhancing plant dry weights, especially with increasing the application rate from 5 to 10 mL kg −1 . Although several reports highlighted the implication effects of HS on plant growth [10,[61][62][63], the results obtained herein indicate that these efficiencies were low…”
Section: Effect Of the Used Organics And Their Ha And Fa Extracts On Plant Growth Parameterscontrasting
confidence: 68%
See 1 more Smart Citation
“…The application of humic acid seemed to be preferred over fulvic acid in enhancing plant dry weights, especially with increasing the application rate from 5 to 10 mL kg −1 . Although several reports highlighted the implication effects of HS on plant growth [10,[61][62][63], the results obtained herein indicate that these efficiencies were low…”
Section: Effect Of the Used Organics And Their Ha And Fa Extracts On Plant Growth Parameterscontrasting
confidence: 68%
“…The application of humic acid seemed to be preferred over fulvic acid in enhancing plant dry weights, especially with increasing the application rate from 5 to 10 mL kg −1 . Although several reports highlighted the implication effects of HS on plant growth [10,[61][62][63], the results obtained herein indicate that these efficiencies were low when compared with the corresponding ones attained due to the application of the organic amendments from which they were extracted (compost and biogas). Most likely, these results highlight the need for the application of higher amounts of HS, which is not a practical agricultural process and at the same time requires additional costs.…”
Section: Effect Of the Used Organics And Their Ha And Fa Extracts On Plant Growth Parameterscontrasting
confidence: 67%
“…A significant Pearson correlation was found between the contents of chlorophylls A and B with the leaf area (Figure 8), showing that plants with a higher concentration of chlorophylls provide a greater leaf area in the plant, start to carry out more photosynthesis and thus fix more carbon dioxide, which can provide an increase in the dry mass of the plant, so the use of herbicides that act on the photosystems directly influences the development of the plant, according to the Table 2. This increase in the concentration of chlorophyll also guarantees an increase in the nitrogen content (Table 2), a fact that the rate of mineralization of organic nitrogen in humic and fuvic acids varies with the interaction of the pH in the soil that becomes available for the plant (Sherrod et al, 2019, Pérez-Esteban et al, 2019, Karčauskienė et al 2019, therefore, a statistical difference was observed in the concentration of organic nitrogen (N-org) in cotton leaves, where again the use of agricultural gypsum (1.5 t ha -1 ) with golden mussel shell powder (1.5 t ha -1 ) had the highest average, which was approximately 23.79% higher than the treatment using snail shell powder (3.0 t ha -1 ), as shown in Figure 9. CV (%): 10,53.…”
Section: )mentioning
confidence: 99%
“…HAs are dark (carbon rings and chains) [36] FAs are tight yellow to golden yellow [37] HAs are not soluble in acidic conditions, and they are soluble in alkaline conditions [36] FA are soluble in acidic and alkaline conditions [36] HAs unlock nutrients and bind to them, thereby making them available for uptake by plants [36] FAs bind to nutrients and transfer them to plants [37] HAs have a higher molecular weight (1500−5000 Daltons in streams and from 50,000−500,000 Daltons in soils) [38] FAs are characterized by relatively low molecular weight [39] HAs contain oxygen, nitrogen, hydrogen, and phosphorus [33] FAs are more biologically active: the oxygen is twice that of Humic acids [37] HAs have aromatic rings in a molecule [40] FAs have many functional groups (hydroxyl and carbonyl groups) [37] They are less polar and more hydrophobic than fulvic acids [40] These groups make FA polar [40] The physical shapes of HAs molecules are determined by pH value, ionic strength of a solution and metal ions. HAs are negatively charged [41] FAs are negatively charged.…”
Section: Humic Acids (Ha) Fulvic Acids (Fa)mentioning
confidence: 99%